Clash of the generations - Grubb, Valerie M. (New York Wiley, 2017)
"Case studies and strategies for more effective multi-generational management Clash of the Generations explores this new and increasingly common workplace phenomenon, and provides strategies to help managers navigate this ever more complex maze. Traditionally, older workers would retire and make room for the next generation; instead, Baby Boomers are now prolonging their time in the workplace, yet the successive generations are still coming in. Senior leaders are now left to manage a blended workplace comprised of up to four generations--each with their own ideas of work ethic, work/life balance, long-term career goals, and much more. Management is challenging at the best of times, but the new prevalence of generation gaps--sometimes even layered--add an entirely new dimension to an already complex responsibility. This book presents case studies and interviews with representatives of companies with age-diverse workforces, detailing innovative strategies for smoothing out the bumps and helping everyone work together. Managers have long wished that their positions came with an instruction manual, and this book delivers with a host of effective inter-generational management strategies illustrated by real-world companies. Manage the multi-generation workplace more effectively Navigate the generational culture clash Adopt proven strategies for helping everyone get along Promote a more positive culture amidst clashing expectations Every generation in the workplace has value, each has their own strengths, their own weaknesses, and their own unique talents. Each is indispensable, and when they come together as a synergistic force, they can be unstoppable. Effective management means bringing out the best in your workforce, and the strategies presented in Clash of the Generations help you streamline your varied workforce into a team more valuable than the sum of its parts"--
"Clash of the Generations details proven strategies that managers and senior leaders can employ to ensure that everyone gets along in the sandbox"--
Machine generated contents note: Preface Acknowledgments Chapter 1: The New Workplace Reality The Changing Nature of Leadership The Changing Role of the Manager The Changing Role of HR The Changing Role of the Employee Building on These Changes Chapter 2: Defining the Generations What the Experts Say The Big Three--and a Newcomer Generational Characteristics The More Things Change Chapter 3: Fostering a Culture of Inclusion The Business Case for Diversity The Role of Company Culture Overcoming a Negative Culture Creating an Age-Diverse Culture Chapter 4: Setting the Stage for Great Performance Goal Setting Evaluating Employee Performance You Get What You Reward Senior Leadership versus Peer-to-Peer Recognition The Basics of Recognition Intrinsic Motivators Career and Development Recognition Chapter 5: Being an Inclusive Manager The Benefits of Inclusion Breaking Bad Habits False Thinking of New Managers Lead by Example Don't Emulate Bad Managers Promoting Respect Innovation at Both Ends of the Spectrum Managing Workers Older than You The Consequences of Not Being Inclusive Chapter 6: Promoting Growth Opportunities The Power of Effective Delegation Empower Your Employees Accommodating Different Learning Styles Experiential Training Establish a Mentoring Program Chapter 7: Managing Differences in Work Ethic Defining Ethics The Importance of Mission to Millennials Connecting Company Mission and Ethics Goals What Managers Can Do What Companies Can Do Chapter 8: Managing Differences in Work-Life Balance Expectations The Birth of Work-Life Balance Work-Life Blending versus Balancing Measuring Performance versus Face Time Managing Flexibility Managing Virtual Teams Chapter 9: Managing Differences in Career Development Planning Expectations of Career Development by Generation Using Career Development for Succession Planning at All Levels Five Easy Steps to Creating a Career Plan Creating a Company-Wide Development Program Specific to Leadership Creating Your Own Career Development Plan Chapter 10: Generational Give and Take Communication Is Key The How and When of Communication Appreciating the Contributions of Youth Valuing the Wisdom of Age Promoting Positive Interactions The Challenge of the Young Leading the Wise Chapter 11: You as the Motivating Force Expectations of Today's Manager Focusing on You Finding a Mentor Moving from Tactical Doer to Strategic Thinker Chegg Background Benefits Company Culture Physical Work Environment Recruiting Summary Consultants: Leadership Development Services, LLC and RGP Interviewees Leadership Flexibility Work Ethic and Style Benefits Electronic Arts Background Company Culture Career Development Recruiting Summary Hy-Ko Products Background Benefits & Recruitment Career Development Summary TECT Corporation Background Recruitment Company Culture Career Development Summary The Andersons Background Company Culture Physical Work Environment Career Development Benefits Summary Author Bio References.
Keywords: Diversity in the workplace; Conflict of generations in the workplace; Intergenerational relations; Older people; Youth; BUSINESS & ECONOMICS / Human Resources & Personnel Management